Exploring temporality in socio-ecological resilience through experiences of the 2015–16 El Niño across the Tropics. (March 2019) - Whitfield, Stephen; Beauchamp, Emilie; Boyd, Doreen S.; Burslem, David; Byg, Anja; Colledge, Francis; Cutler, Mark E.J.; Didena, Mengistu; Dougill, Andrew; Foody, Giles; Godbold, Jasmin A.; Hazenbosch, Mirjam; et al.
Highlights: El Nino impacts on six socio-ecological systems are described. Diverse experiences of 2015–16 El Nino event across these systems. System resilience shaped by interaction of short and long term processes. El Nino experiences provide window for analysing long term resilience. Abstract: In a context of both long-term climatic changes and short-term climatic shocks, temporal dynamics profoundly influence ecosystems and societies. In low income contexts in the Tropics, where both exposure and vulnerability to climatic fluctuations is high, the frequency, duration, and trends in these fluctuations are important determinants of socio-ecological resilience. In this paper, the dynamics of six diverse socio-ecological systems (SES) across the Tropics – ranging from agricultural and horticultural systems in Africa and Oceania to managed forests in South East Asia and coastal systems in South America – are examined in relation to the 2015–16 El Niño, and the longer context of climatic variability in which this short-term 'event' occurred. In each case, details of the socio-ecological characteristics of the systems and the climate phenomena experienced during the El Niño event are described and reflections on the observed impacts of, and responses to it are presented. Drawing on these cases, we argue that SES resilience (or lack of) is, in part, a product of both long-term historical trends, as well as short-term shocks within this history. Political and economic lock-ins and dependencies, and the memory and social learning that originates from past experience, all contribute to contemporary system resilience. We propose that the experiences of climate shocks can provide a window of insight into future ecosystem responses and, when combined with historical perspectives and learning from multiple contexts and cases, can be an important foundation for efforts to build appropriate long-term resilience strategies to mediate impacts of changing and uncertain climates.